Hospitalization, Asthma Phenotypes, and Readmission Rates in Pre-school Asthma - Donath, Helena; Kluge, Sven; Sideri, Georgia; Trischler, Jordis; Jerkic, Silivija P.; Schulze, Johannes; Zielen, Stefan; Blumchen, Katharina (Frontiers in Pediatrics, 2020)
Objective: Children with pre-school asthma suffer disproportionally more often from severe asthma exacerbations with emergency visits and hospital admissions compared to school children. Despite this high disease burden, there are only a few reports looking at this particular severe asthma cohort. Similarly, there is little real-life research on the distribution of asthma phenotypes and personalized treatment at discharge in this age group. Patients and Methods: Retrospective analysis of the electronic charts of all children aged 1–5 years with asthma hospitalizations (ICD J45) at the Frankfurt University between 2008 and 2017. An acute severe asthma exacerbation was defined as dyspnea, oxygen demand, and/or systemic steroid therapy. Age, gender, duration of hospitalization, asthma phenotype, treatment, and readmission rate were analyzed. Results: Of 572 patients, 205 met the definition of acute severe asthma. The phenotypic characterization showed 56.1% had allergic asthma, 15.2% eosinophilic asthma and 28.7% non-allergic asthma. Of these patients, 71.7% were discharged with inhaled corticosteroids (ICS) or ICS + long-acting-beta-agonists (LABA), 15.1% with leukotriene antagonists (LTRA) and 7.3% salbutamol on demand. The rate of emergency presentations (emergency department and readmission) within 12 months after discharge was high (n = 42; 20.5%). No phenotype tailored treatment was detectable. Neither the number of eosinophils (>300/μl) nor the treatment at discharge had an effect on emergency visits and readmission rate. Conclusion: Despite protective therapy with ICS, ICS + LABA, or LTRA, the readmission rate was high. Thus, current care and treatment strategies should be reevaluated continuously, in order to better control asthma in pre-school children and prevent hospitalization.